2001
DOI: 10.1017/s0074180900219670
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Different Coronal Streamers

Abstract: In this paper a summary of results from coordinated observations of streamers acquired by the SOHO Coronal Diagnostic Spectrometer (CDS) and Ultra Violet Coronograph Spectrometer (UVCS) experiments is presented (Parenti et al. 2000). Data from different altitudes within the solar corona were taken, with the purpose of determining their physical parameters – densities, electron temperatures and element abundances – and their changes over the altitude range between 1.02 and 1.6 R⊙. Further UVCS streamer data, ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 2 publications
7
50
2
Order By: Relevance
“…These density values are systematically lower than those derived by LASCO C2 pB data inversion, in some cases even a factor of five lower. At low heliocentric distances, they are in good agreement with the densities obtained by the method of Parenti et al (2000), with an O vi disc intensity input equal to the quiet-Sun value reported by Vernazza & Reeves (1978).…”
Section: Diagnostics Of Physical Parameterssupporting
confidence: 86%
See 4 more Smart Citations
“…These density values are systematically lower than those derived by LASCO C2 pB data inversion, in some cases even a factor of five lower. At low heliocentric distances, they are in good agreement with the densities obtained by the method of Parenti et al (2000), with an O vi disc intensity input equal to the quiet-Sun value reported by Vernazza & Reeves (1978).…”
Section: Diagnostics Of Physical Parameterssupporting
confidence: 86%
“…Moreover, the disc intensity of the O vi 1032 Å line was used in Eq. (8) of Parenti et al (2000) to determine the electron density at heliocentric distances lower than 2.25 R . As for the Lyα line, we adopted the average chomospheric profile reported by Gouttebroze et al (1978), which agrees, within the uncertainties, with the full-disc Lyα intensities measured by the spectrometer SOLSTICE (SOLar STellar Irradiance Comparison Experiment) on the UARS satellite (see Woods et al 2000) during the week of our observations.…”
Section: Observations and Data Analysismentioning
confidence: 99%
See 3 more Smart Citations